Ulcerative Colitis in a Bangladeshi Child: A Case Report (BIRDEM Medical Journal, 2019)
Introduction: Ulcerative colitis (UC) is a chronic idiopathic inflammatory disorder of colon. Ulcerative colitis is uncommon in tropics and sub-tropics. We describe a case of pediatric ulcerative colitis with successful treatment. A 4-years-old girl who presented with passage of loose bloody stool, abdominal pain and mild arthralgia along with significant weight loss. Her height was 95 cm, and weight was 13 kg. Diagnosis was confirmed by colonoscopy and histopathology. Treatment was thereafter started with parenteral steroid initially then oral steroid and mesalamine. The patient is now on remission and is on regular follow up. UC is rare in Bangladesh, especially in children. Several conditions like infective colitis, allergic colitis, Meckel’s diverticulitis, Crohn’s disease, etc. may mimic the features of UC. So, if a child presents with recurrent bloody diarrhea, UC should be considered as a differential diagnosis.Birdem Med J 2019; 9(1): 89-94